A trajetória do curso de medicina da Universidade de Passo Fundo e a consolidação de Passo Fundo como polo de saúde - Dutra, Jorge Luis Michura (2025)
This research explores the history of the creation of the Medicine course at the University of Passo Fundo (UPF) and its fundamental role in transforming the city into a regional center for health services. The study covers everything from the first efforts to establish higher education in Passo Fundo in the 1950s to the consolidation of UPF and the subsequent creation of the much-desired Medicine course. The work narrates the moment of hesitation and the ultimatum from the federal government that spurred the decision to create the course, which faced significant obstacles, including the need to adapt the faculty and infrastructure to meet the requirements of the Ministry of Education and Culture (MEC). Added to this is the process of transforming Passo Fundo into a regional center for health services, highlighting the contribution of the UPF Medicine course to this development. The improvement of hospitals and specialized clinics, the performance of medium and high complexity procedures, and the reputation for excellence in health services consolidated the city's identity as a medical reference center. This work analyzes the socioeconomic impact of the presence of the Medicine course in Passo Fundo, including the increase in the number of doctors, the attraction of patients from other regions, the development of other service sectors, and job creation, as well as the opening of other Medicine courses in the city and the evolution of health infrastructure over the years. In conclusion, the work demonstrates how the creation of the Medicine course at UPF was a crucial milestone for the development of Passo Fundo, transforming it into a recognized health hub throughout the state and the country. The initiative not only trained qualified health professionals, but also boosted the economic and social growth of the region, consolidating the city's identity as a medical reference center.